L’autopsie de Napoléon Bonaparte. Mise au point anatomo-pathologique pour le bicentenaire de la mort de Napoléon Ier sur l’île de Sainte-Hélène en 1821 - Lugli, Alessandro; Carneiro, Fatima; Dawson, Heather; Fléjou, Jean François; Kirsch, Richard; van der Post, Rachel; Vieth, Michael; Svrcek, Magali (Annales De Pathologie, 2021)
Napoleon Bonaparte died on 5 May 1821 on the island of St Helena after almost six years of exile. The next day, Dr Francesco Antommarchi, a Corsican doctor chosen by the Bonaparte family to treat the exiled emperor, performed the autopsy in the presence of sixteen people, including seven British doctors. Two hundred years after the event of 6 May 1821, the cause of Napoleon's death is still a mystery. Various hypotheses, such as arsenic intoxication, cardiac arrhythmia or, more recently, anaemia caused by gastrointestinal haemorrhage associated with chronic gastritis, have been put forward in the medical-historical literature. The main reasons for all these debates and misunderstandings are the presence of several autopsy reports, their often unscientific interpretation, as well as a certain taste for mystery. However, from a scientific point of view, the question arises as to whether autopsy reports are really conclusive as to the real cause of death. Thus, on the occasion of the bicentenary of Napoleon I's death in St. Helena, an international group of anatomo-pathologists specialising in digestive pathology set themselves the goal of analysing Napoleon I's autopsy reports according to their level of medical evidence (high, moderate and low). The autopsy reports of 1821 support the hypothesis of advanced malignant neoplasia of the stomach associated with gastric haemorrhage as the immediate cause of Napoleon I's death on 5 May 1821.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Autopsy; Bicentennial; Gastric cancer; Gastritis; Napoleon I